Diplomasi Budaya melalui Nation Branding Wonderful Indonesia di Era New Normal Tourism - Yulliana, Engga Ayu (Global and Policy Journal of International Relations, 2021)
ABSTRACT Tourism is the leading sector in the largest foreign exchange earner after the palm oil industry. The prospects for growth in Indonesian tourism are strongly supported by cultural diversity and local wisdom that characterizes the nation. The achievement of tourism must be dashed due to the impact of the Covid-19 pandemic which caused a decrease in tourist visits in the January-June 2020 period by 59.86 percent. This study aims to examine the cultural diplomacy strategy through the nation branding wonderful Indonesia in order to restore national tourism in the new normal era. The method used in this research is literature study using secondary data support. The results of the discussion show that efforts to promote the nation's culture and local wisdom have long been reflected in the Wonderful Indonesia logo brand which was then officially designated as the master tourism brand in 2016. Wonderful Indonesia reflects the nation's commitment to the quality of tourist destinations in Indonesia. The cultural diplomacy approach in the nation branding wonderful Indonesia was then adapted to a new pattern through the digitalization of tourism which involved public diplomacy and digital diplomacy. The transformation of the logo brand has also changed with a new slogan in the form of toughtful Indonesia which is in line with the call to carry out activities from home only. The digitalization of tourism encourages the existence of new normal tourism which then creates a new tourism activity transformation in the form of solo travel activities, virtual reality tourism, and staycation. Keywords : Cultural diplomacy, Wonderful Indonesia, New Normal Tourism  DOI : https://doi.org/10.33005/jgp.v9i1.2409